Rough Guides phrasebook Portuguese (Rough Guide phrasebook, 2019)
Compact, clear, and packed with key words and phrases to help conversation, this pocket-sized Portuguese phrasebook and dictionary from Rough Guides' trusted language experts (with free app) is a trusty travel companion, and all you need to make yourself understood - and to understand others - when you're out and about in Portugal and other Portuguese-speaking countries.